Enzyme and lipid markers in relation to cardiovascular risk in postmenopausal women - Klisić, Aleksandra; Mercantepe, Filiz; Bakić, Mirjana; Ninić, Ana (Archives of Pharmacy, 2025)
Postmenopausal women are at an increased risk of cardiovascular disease (CVD), the leading cause of death worldwide, compared with younger women. Gamma-glutamyl transferase (GGT) and high-density lipoprotein cholesterol (HDL-c) are linked with oxidative stress, inflammation, insulin resistance, and CVD risk factors. However, there have been no studies that examined the relationship between GGT/HDL-c and CVD exclusively in women who are not of reproductive age. Therefore, we aimed to examine this potential relationship in a cohort of CVD-free postmenopausal women. A total of 150 disease-free postmenopausal women were consecutively included. CVD risk was defined according to high sensitivity C-reactive protein (hsCRP) concentration (hsCRP < 1 mg/L defines low risk and hsCRP ≥ 1 mg/L defines intermediate and high risk). The GGT/HDL-c was independently associated with intermediate and high CVD risk in postmenopausal women. As this enzyme/lipid index increased by 1 unit, the probability of intermediate and high CVD risk rose by 10.3% (OR = 1.103, p = 0.024). The GGT/HDL-c ratio was independently associated with higher CVD risk, as measured with hsCRP in postmenopausal women. This cost-effective, easily measured, and widely available index could be used in everyday clinical practice for estimating CVD risk in postmenopausal women.
Keywords: cardiovascular risk; gamma-glutamyl transferase; lipoproteins; postmenopausal